Biosynthetic Labeling and Two‐Color Imaging of Phospholipids in Cells. Issue 3 (13th January 2015) - Jao, Cindy Y.; Roth, Mary; Welti, Ruth; Salic, Adrian
Abstract Phospholipids with a choline head group are abundant components of all biological membranes, performing critical functions in cellular structure, metabolism, and signaling. In spite of their importance, our ability to visualize choline phospholipids in vivo remains very limited. We present a simple and robust chemical strategy to image choline phospholipids, based on the metabolic incorporation of azidocholine analogues, that accurately reflects the normal biosynthetic incorporation of choline into cellular phospholipids. Azidocholine‐labeled phospholipids can be imaged in cells with high sensitivity and resolution, following derivatization with fluorophores, by bio‐orthogonal chemical reactions compatible with live‐cell imaging. We used this method to visualize the subcellular localization of choline phospholipids. We also demonstrate that double metabolic labeling with azidocholine and propargylcholine allows sensitive two‐color imaging of choline phospholipids. Our method represents a powerful approach to directly image phospholipids, and to study their dynamics in cells and tissues.